2010
DOI: 10.1021/ma102036h
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal Crystallization Behaviors of Nanocomposites Prepared by In Situ Polymerization of High-Density Polyethylene on Multiwalled Carbon Nanotubes

Abstract: Thermal properties and nonisothermal crystallization kinetics of polyolefin nanocomposites (high-density polyethylene/multiwalled carbon nanotubes) were characterized by differential scanning calorimetry and thermogravimetric analysis. In situ metallocence polymerization was used to prepare nanocomposites of multiwalled carbon nanotubes (MWCNTs) and high-density polyethylene (HDPE). This polymerization method consists of attaching a metallocene catalyst complex onto the surface of the MWCNTs followed by surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…The normal spherulitic morphology does not appear in polarized optical micrographs; instead the crystallites appear as elongated entities that are consistent with an entirely transcrystalline or NHSK structures. 129 However, another study, also with metallocene-grafted HDPE, found a significant increase in the crystallization rate while also finding a substantial decrease in the Avrami exponent n. This study also found significantly thicker crystals as measured by a successive self-nucleation and annealing thermal fractionation technique performed in a DSC. 260 Both studies found that the fractional crystallinity initially increased to $10% nanotube content, then decreased as the nanotube content increased above 10%.…”
Section: Semicrystalline Polymersmentioning
confidence: 49%
“…The normal spherulitic morphology does not appear in polarized optical micrographs; instead the crystallites appear as elongated entities that are consistent with an entirely transcrystalline or NHSK structures. 129 However, another study, also with metallocene-grafted HDPE, found a significant increase in the crystallization rate while also finding a substantial decrease in the Avrami exponent n. This study also found significantly thicker crystals as measured by a successive self-nucleation and annealing thermal fractionation technique performed in a DSC. 260 Both studies found that the fractional crystallinity initially increased to $10% nanotube content, then decreased as the nanotube content increased above 10%.…”
Section: Semicrystalline Polymersmentioning
confidence: 49%
“…So far, most CNTs-grafted polymers are non-crystallizable. Several examples for CNTs-grafted crystallizable polymers include polyamide [31,32], poly(ε-caprolactone) (PCL) [33e37], poly(ethylene oxide) [38], poly(L-lactide) (PLLA) [39e45], polyethylene [46], poly(3-hexylthiophene) [47], poly(adipic acidhexamethylene diamine) [48], poly(ether ether ketone) [ [27]. The grafted catalyst was used to polymerize L-LA and ε-CL.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated average value of the Avrami exponent, n, from Figure 4 is approximately 2.56 for HDPE/MWCNT (1.5 wt%) nanocomposite, 1.99 for HDPE/MWCNT (2.4 wt%) nancomposite and 1.78 for HDPE/MWCNT (7.3 wt% close to that of the percolation threshold 28 ) nancomposite ( Table 1). 10 At the beginning of the process, faster crystallization proceeds due to the nucleating action of the MWCNT surface. In the absence of MWCNT, HDPE forms large spherulites (20~50m) with slightly twisted lamellae ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%